2017
DOI: 10.1039/c7ob01448a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical optimization of macrocyclic HIV-1 inactivators for improving potency and increasing the structural diversity at the triazole ring

Abstract: HIV-1 entry inhibition remains an urgent need for AIDS drug discovery and development. We previously reported the discovery of cyclic peptide triazoles (cPTs) that retain the HIV-1 irreversible inactivation functions of the parent linear peptides (PTs) and have massively increased proteolytic resistance. Here, in an initial structure-activity relationship investigation, we evaluated the effects of variations in key structural and functional components of the cPT scaffold in order to produce a platform for deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…The CD4mc were analyzed, dissolved in dimethyl sulfoxide (DMSO) at a stock concentration of 10 mM, aliquoted, and stored at Ϫ80°C. Cyclic peptide triazoles (cPTs) AAR029N2 and AAR029N3 were synthesized, purified (Ͼ95% homogeneity by reverse-phase HPLC), and structurally validated as previously described (73,74). The cPTs were analyzed, dissolved in DMSO at a stock concentration of 10 mM, aliquoted, and stored at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD4mc were analyzed, dissolved in dimethyl sulfoxide (DMSO) at a stock concentration of 10 mM, aliquoted, and stored at Ϫ80°C. Cyclic peptide triazoles (cPTs) AAR029N2 and AAR029N3 were synthesized, purified (Ͼ95% homogeneity by reverse-phase HPLC), and structurally validated as previously described (73,74). The cPTs were analyzed, dissolved in DMSO at a stock concentration of 10 mM, aliquoted, and stored at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, since changes in the gp120 inner domain layers in combination with changes at position 375 have a global effect on the CD4BS, we tested the sensitivity of our panel of CRF01_AE Env mutants to another class of Env antagonists targeting the CD4BS: cyclic peptide triazoles (cPTs) (73,74). Again, the introduction of the LM mutations in combination with a small residue at position 375 (LMϩHS and LMϩHT) in a CRF01_AE Env was found to dramatically increase the sensitivity to neutralization by all cPTs tested (AAR029N2 and AAR029N3) (Fig.…”
Section: Figmentioning
confidence: 99%
“…After cleavage and reverse‐phase HPLC purification, the N‐terminal AAR029b was reacted with FITC in DMF at room temperature to yield the FITC‐AAR029b that was purified using reverse‐phase HPLC. The N‐terminal was chosen for labeling based on previous observations which showed the solvent exposure of the N‐terminus.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a subclass of PTs, with a free Cys residue at the C terminus of PT and denoted peptide triazole thiols (PTTs), causes virus membrane lysis and release of luminal capsid protein p24 . More recently, small potent cyclic PTs (cPTs) were identified that hold great potential as anti‐HIV‐1 therapeutic leads. The added value of cPTs over linear PTs is that they are more resistant to proteolytic degradation while retaining high affinity and specificity for interaction with target envelope HIV‐1 glycoprotein gp120 and at the same time exhibiting no cellular toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] Among different triazoles, 1,2,3triazoles particularly have a broad range of applications in the field of pharmaceutical and medicinal chemistry, and they are a part of many molecules reported as antidiabetic. [17][18][19][20][21][22][23][24] It has been reported that benzimidazole compounds, that is, 2-aryl benzimidazoles (A) and 2-(2chlorophenyl)-7-methyl-1H-benzo [d]imidazole (B), act as α-glucosidase inhibitors, [25][26][27] but there is still a need to discover some new analogs for improved inhibitory activity. Various studies have reported that by combining a benzimidazole ring with an electron-withdrawing group such as triazole, the biological activity gets enhanced.…”
Section: Introductionmentioning
confidence: 99%